2012
DOI: 10.1242/dev.081703
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative and antagonistic roles for Irx3 and Irx5 in cardiac morphogenesis and postnatal physiology

Abstract: SUMMARYThe Iroquois homeobox (Irx) homeodomain transcription factors are important for several aspects of embryonic development. In the developing heart, individual Irx genes are important for certain postnatal cardiac functions, including cardiac repolarization (Irx5) and rapid ventricular conduction (Irx3). Irx genes are expressed in dynamic and partially overlapping patterns in the developing heart. Here we show in mice that Irx3 and Irx5 have redundant function in the endocardium to regulate atrioventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 49 publications
2
88
2
Order By: Relevance
“…Genes in equivalent positions within these clusters (Irx1/Irx3, Irx2/Irx5, Irx4/Irx6) are paralogues and therefore most similar; however, partial functional compensation has been described even for nonparalogous Irx genes, for example in heart formation (40). Defects in brain patterning have been observed in the Fused toes mouse mutant that carries a chromosomal deletion eliminating the IrxB cluster (41); however, thalamic specification seems relatively normal in these mice, consistent with Irx1 being the major mediator of thalamic competence in rodents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes in equivalent positions within these clusters (Irx1/Irx3, Irx2/Irx5, Irx4/Irx6) are paralogues and therefore most similar; however, partial functional compensation has been described even for nonparalogous Irx genes, for example in heart formation (40). Defects in brain patterning have been observed in the Fused toes mouse mutant that carries a chromosomal deletion eliminating the IrxB cluster (41); however, thalamic specification seems relatively normal in these mice, consistent with Irx1 being the major mediator of thalamic competence in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Irx proteins contain an acidic activation domain, suggesting that they may function as transcriptional activators (40,42). However, Xenopus irx1 was shown to operate as a transcriptional repressor in neural plate specification in frogs (39).…”
Section: Discussionmentioning
confidence: 99%
“…Several T-box and Iroquois homeobox transcription factors, which regulate cardiac development, have been shown to pattern areas of ion channel expression throughout the heart and parts of the conduction system (Boukens & Christoffels, 2012; Zhang et al, 2011; Gaborit et al, 2012; Bakker et al, 2008; Oyamada et al, 2013; Wiese et al, 2009). A central component of the cardiac conduction system is the sinoatrial node (SAN), which functions as the pacemaker to set the heartbeat.…”
Section: Multilayered Regulation Of Cx43 Biogenesismentioning
confidence: 99%
“…During our study on sexual differentiation, we set out to generate Irx3 / Irx5 double mutant mice to analyze the phenotype in developing gonads because both genes are expressed in female but not in male developing gonads [13] and the gene products are functionally redundant [14, 15]. Previously, it has been reported that Irx3 / Irx5 double knockout (dKO) mice generated by gene targeting using embryonic stem cells exhibited heart and early hindlimb bud defects and were embryonic lethal at 14.5 days post coitum (dpc); however, the gonadal phenotype was not described [14, 15].…”
mentioning
confidence: 99%
“…Previously, it has been reported that Irx3 / Irx5 double knockout (dKO) mice generated by gene targeting using embryonic stem cells exhibited heart and early hindlimb bud defects and were embryonic lethal at 14.5 days post coitum (dpc); however, the gonadal phenotype was not described [14, 15]. Here, we have identified mutant mice with a 0.5 Mb deletion generated unintentionally in the course of Irx3 / Irx5 dKO production by the CRISPR/Cas9 system.…”
mentioning
confidence: 99%